Produksi dan Kualitas Kolostrum dan Susu Kolostrum pada Sapi Perah yang Mengkonsumsi Daun Katuk Depolarisasi - Afton Atabany; Agik Suprayogi; Muladno Muladno; Fadjar Satrija; Ronald Tarigan; Welly Sugiono; Yuliantony Queen (Institut Pertanian Bogor, 2022)
This study aims to determine the effect of additional feed with depolarizing katuk leaves on the production and quality of colostrum and colostrum milk in Friesian Holstein dairy cows. There were 21 dairy cows that had just giving birth, divided into 3 groups of 7 each, namely the control group (complete feed), BKD (complete feed added with Depolarizing Katuk Powder), PKD (complete feed added with Depolarizing Katuk Pellet). Depolarizing katuk feed was given 100 grams per head per day as a feed additive. Parameters observed were feed consumption, production and quality of colostrum and colostrum milk. The results showed that there was no difference in the consumption of feed supplemented with depolarizing katuk leaves, colostrum production, milk density, total solid colostrum, Solid non-fat, lactose contents, and protein contents of colostrum and colostrum milk compared to the control group. Significant differences occurred in colostrum milk production, total solid colostrum milk, and fat content of colostrum and colostrum milk. It was concluded that depolarizing katuk leaves could be used as additional feed to increase the production and total solids of colostrum milk, and increase the fat content of colostrum and colostrum milk. Keywords: colostrum, colostrum milk, depolarizing katuk leaf, Friesian Holstein